2019
DOI: 10.2147/ceg.s175061
|View full text |Cite
|
Sign up to set email alerts
|

<p>Eosinophilic esophagitis: early diagnosis is the key</p>

Abstract: Eosinophilic esophagitis (EoE) is a disorder which affects all ages, from infancy through adulthood. It typically affects atopic individuals (Table 1) and is a chronic allergic disorder, with foods ubiquitous in the diet being the most described trigger of this isolated eosinophilic inflammation of the esophagus in both adults and children. This inflammatory process leads to esophageal symptoms such as dysphagia and feeding intolerance. In this review, we provide a brief overview of the current state of EoE th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 79 publications
0
24
0
2
Order By: Relevance
“…The most common symptoms of EoE, such as dysphagia and food impaction, increase with age and are more common during adolescence. Concomitant atopic conditions should increase the suspicion of EoE [ 33 ]. It is diagnosed on the basis of symptoms of esophageal disfunction and >15 eosinophils per high power field (eos/hpf) on esophageal biopsy [ 34 , 35 ].…”
Section: Clinical Features Of Non-ige Gastrointestinal Famentioning
confidence: 99%
“…The most common symptoms of EoE, such as dysphagia and food impaction, increase with age and are more common during adolescence. Concomitant atopic conditions should increase the suspicion of EoE [ 33 ]. It is diagnosed on the basis of symptoms of esophageal disfunction and >15 eosinophils per high power field (eos/hpf) on esophageal biopsy [ 34 , 35 ].…”
Section: Clinical Features Of Non-ige Gastrointestinal Famentioning
confidence: 99%
“…The impact of EoE on healthrelated QOL has been shown to increase with disease severity. 2 For example, in a study conducted between March 2013 and May 2014, patients with EoE for at least 17 years who needed an endoscopy for diagnosis, further confirmation of a suspected diagnosis, or monitoring of previously diag nosed EoE were invited to recall their QOL and symptom severity over the last 7 days using validated instruments. 43 Results indicated that the presence of dysphagia was correlated with decreased QOL and increased disability.…”
Section: Humanistic Burdenmentioning
confidence: 99%
“…Eosinophilic esophagitis (EoE) is a progressive, chronic inflam matory disease that is associated with a substantial disease burden and longterm complications. 1,2 Early and accurate diagnosis of EoE is critical for preventing worsening, potentially irreversible damage to the esophagus. 2 Esophageal remodeling, narrowing, and fibrosis can occur when EoE is inadequately controlled; the dura tion of untreated disease is the strongest predictor of eso phageal stricture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported in this review, most patients were normal weight or even obese. A meticulous evaluation of the patient’s symptoms should be recommended, and the clinician should ask the right questions to detect suspicious eating habits ( Table 6 ) [ 59 ].…”
Section: Management Of Egids Patients: From Traditional Tools and mentioning
confidence: 99%